Concept and Implementation Merdeka Belajar Curricu-lum in Higher Education - Muhammad Ade Kurnia Harahap; Bambang Ismaya; Abdul Wahab; Susatyo Adhi Pramono; Ichsan Ichsan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The government has implemented numerous policies to improve educational quality, such as the independent learning policy. Educational institutions are no less lagging behind in terms of improving educational quality. The descriptive qualitative method was used in this research. The sources used are from scientific books, academic article, journal that has been published in line with the main issue. The results of this study show that the implementation and the concept of the independent learning policy in higher educational level aims to improve the quality of education through the learning process, commitment from teachers, as well as creativity and support from school principals.